Prospects of development of acid–resistant hybrid cements on the basis of alkaline–activated binders - Zozulynets, V.; Kovalchuk , O. (Ways to Improve Construction Efficiency, 2022)
Quite often during operation, construction products and structures are exposed to aggressive environments, which leads to a decrease in their physical and mechanical characteristics and durability in general. To date, there is a wide range of options for eliminating the effects of structural failure, and new recommendations are being developed to prevent destructive processes that take place in the body of artificial cement stone. The issue of improving the acid resistance of building materials is no exception. Unfortunately, the existing acid–resistant materials, although characterized by high resistance to operation in acidic environments, but under the influence of water and with the change of environment to neutral or alkaline, they are also destroyed. This applies directly to acid–resistant materials based on liquid glass. An analysis of existing research has confirmed the effectiveness of using alkaline–activated binder systems as a basis for acid–resistant cements especially when comparing them with Portland cement. This is primarily due to the difference in the phase composition of their cement stone, which is characterized by the absence of highly basic hydrosilicates of calcium, etringite, free lime and the presence of alkaline and alkaline earth hydrosilicate and hydroaluminosilicate neoplasms. The latter, as research experience has shown, provide improved performance properties of materials based on alkaline–activated binders. They are also characterized by increased acid resistance. Thus, the main task of research is to determine the optimal ratio in the cement stone of the hybrid composition of the phases of the systems систем СaO – SiO2 – H2O; Na2O – CaO – Al2O3 – SiO2 – H2O and Na2O – Al2O3 – SiO2 – H2O, which will provide both hydrating properties of the binder and high acid resistance. The concept that clearly reflects the prospects of research is to consider the main factors influencing the formation of acid–resistant phases: "composition – properties – structure – technology". To study the physicochemical conditions of synthesis it is necessary to study model systems of different compositions of R2O – CaO – Al2O3 – SiO2 – H2O, as well as study of technological factors such as component composition, cooking conditions, curing conditions. As a raw material base, it is advisable to use man–made products of industrial production, which are generally represented by slag, ash, etc.